A New Orthodontic Appliance with a Mini Screw for Upper Molar Distalization - Nurhat Ozkalayci; Mehmet Yetmez (Applied Bionics and Biomechanics)
The aim of this study is to present a new upper molar distalization appliance called Cise distalizer designed as intraoral device supported with orthodontic mini screw for upper permanent molar distalization. The new appliance consists of eight main components. In order to understand the optimum force level, the appliance under static loading is tested by using strain gage measurement techniques. Results show that one of the open coils produces approximately 300 gr distalization force. Cise distalizer can provide totally 600 gr distalization force. This range of force level is enough for distalization of upper first and second molar teeth.